Experimental Study on the Dip Angle Effect of Layered Cemented Fillers: A Sandblasting Treatment Applied to Mine Filling - Long Hai; Rongtao Bao (Applied Sciences, 2023)
In order to study the effect of interlayer dip angle on the mechanical properties of tail sand cemented filler and to improve the deterioration of the mechanical properties of the filler caused by delamination, this study introduces the sandblasting method for treating the interface between old and new concretes in concrete science. Two types of delamination, natural delamination and sandblasting delamination, were produced for the tailing sand cemented filler specimens, and the interlayer dip angles were set to 0°, 10°, 20°, and 30°, respectively. Uniaxial compression tests were conducted at maintenance ages of 3 d, 7 d, 14 d, and 28 d, and damage models were established. The results show that (1) the uniaxial compressive strength and modulus of elasticity of the naturally delaminated specimens decrease and then increase with the increase of interlayer dip angle, and reach the lowest at the interlayer dip angle of about 20°. The uniaxial compressive strength and modulus of elasticity of sandblasted delaminated specimens with interlayer dip angle, not more than 20°, can bring positive gains in uniaxial compressive strength and modulus of elasticity, and the stable gains at high age can reach 6.4% and 39.7%, respectively. (2) The post-peak ductility of the two-layered types of specimens increases and then decreases with the increase of the dip angle between layers and reaches the optimum ductility at about 20° of dip angle. (3) The damage of the delaminated filling body is mainly in the form of tensile damage and conjugate shear damage, and the sandblasting treatment can improve the force transmission mode on the delamination surface. (4) Based on the damage evolution of the soil body with Weibull distribution, the damage instantiation model of the layered colluvial filler is constructed, which has high reliability for different interlayer dip angles. Accordingly, the findings of this study demonstrate that the addition of sandblasting can significantly reduce the degradation of the mechanical properties of the tailing sand cemented fill brought on by delamination at a slow dip angle (below 20°), and offer a helpful damage ontology model for use in engineering practice.